Assessment of Safety Integrity Level by simulation of Dynamic Bayesian Networks considering test duration. (January 2019) - Simon, Christophe; Mechri, Walid; Capizzi, Guillaume
Abstract: This paper is devoted to model Safety Instrumented Systems (SISs) availability by Dynamic Bayesian Networks (DBNs). The models integrate several parameters but the main concerns of the study are the integration of test duration and test strategy. The proposed DBN are generic and can be reused for assessing performance and testing the effect of some parameters. More attention has been paid to the performance of the proof test, its harmlessness and particularly its duration. The duration increases the model complexity when considering the components availability given the test but it is more realistic. This parameter should be decided carefully to satisfy the Safety Integrity Level (SIL) objectives. Highlights: Dynamic Bayesian Model is proposed assess the performance of a SIS. Generic building of SIS availability model. Dynamic Bayesian Model considers several parameters of the SIS in low demand mode including proof testing parameters. Impact of test strategy on model structure and performance is discussed.